PENGARUH VARIASI KONSENTRASI BUAH MENGKUDU (Morinda citrifolia) TERHADAP MORTALITAS HAMA KEONG MAS (Pomacea caniculata L.) SEBAGAI SUMBER BELAJAR BIOLOGI - Sukmanah Chomsun; Muhfahroyin Muhfahroyin (Bioedukasi Jurnal Pendidikan Biologi, 2013)
This Reseach aims to study the effect of variation and dose morinda fruit that most effective applicable to mortality gold snail disease, to use product of research as design source study of biologi Junior High School class VIII. Researching on education Laboratory Muhammadiyah Metro of University at November 2012. The design of research employs analisis of varians non-parametrik with Kruskal-Wallis test with four treatments an three time replication. First treatments is control (not having dose), second consentration 50gr/L, third consentration 100gr/L, and fouth consentration 150 gr/L. Product of research to indicated morinda fruit effective to mortality gold snail  disease. Indication is transformation of occured such as descend activity of consume food and mobility, operculum to close, having mucus, not respons, and according  part soft of body to transformation of color to be chalky color or bad color, body of snail to exit for the hard outer layer of body skin, and the gold snail floating on a top suface. This condition indicate that a chemical composite saponin in morinda fruit to affect the process of chemical in a organism, central nerve, and respiration of gold snail.Kata Kunci: Buah mengkudu, mortalitas keong mas, sumber belajar biologi.